Clinical applicability of nursing outcomes in the evolution of orthopedic patients with Impaired Physical Mobility - Marcos Barragan da Silva; Miriam de Abreu Almeida; Bruna Paulsen Panato; Ana Paula de Oliveira Siqueira; Mariana Palma da Silva; Letícia Reisderfer (Universidade de São Paulo, 2015)
AIM: to evaluate the clinical applicability of outcomes, according to the Nursing Outcomes Classification (NOC) in the evolution of orthopedic patients with Impaired Physical MobilityMETHOD: longitudinal study conducted in 2012 in a university hospital, with 21 patients undergoing Total Hip Arthroplasty, evaluated daily by pairs of trained data collectors. Data were collected using an instrument containing five Nursing Outcomes, 16 clinical indicators and a five point Likert scale, and statistically analyzed.RESULTS: The outcomes Body Positioning: self-initiated, Mobility, Knowledge: prescribed activity, and Fall Prevention Behavior presented significant increases in mean scores when comparing the first and final evaluations (p<0.001) and (p=0.035).CONCLUSION: the use of the NOC outcomes makes it possible to demonstrate the clinical progression of orthopedic patients with Impaired Physical Mobility, as well as its applicability in this context.